New exact series for modal green's function - Hamed, Samier M. Ali; Bashir, Saad Osman (IEEE, 2015)
This paper presents a new exact series for modal Green's function that arises when solving the problems of electromagnetic scattering from bodies of revolution. The accuracy and computation time of the series are compared with results from numerical integration. The results using the series are in excellent agreement with those from integration. Moreover, results show that the computation time using the series is better compared to that using the integration.